Effect of Dietary Linoleic Acid (18:2n-6) Supplementation on the Growth Performance, Fatty Acid Profile, and Lipid Metabolism Enzyme Activities of Coho Salmon (Oncorhynchus kisutch) Alevins - Hairui Yu; Lingyao Li; Leyong Yu; Congmei Xu; Jiayi Zhang; Xiangyi Qiu; Yijing Zhang; Lingling Shan (Animals, 2022)
A 12-week feeding trial aimed to evaluate the effects of dietary linoleic acid (LA, 18:2n-6) on the growth performance, fatty acid profile, and lipid metabolism enzyme activities of coho salmon (Oncorhynchus kisutch) alevins. Six experimental diets (47% crude protein and 15% crude lipid) were formulated to contain graded LA levels of 0.11%, 0.74%, 1.37%, 2.00%, 2.63%, and 3.26%. Each diet was fed to triplicate groups of 50 alevins with an initial body weight of 0.364 ± 0.002 g, which were randomly assigned to 18 white plastic tanks (0.8 × 0.6 × 0.6 m, 240 L/tank). Fish were reared in a freshwater flow-through rearing system and fed to apparent satiation four times daily. The survival rate was not significantly different among the treatments (p > 0.05). However, the 1.37% LA group significantly improved the final body weight and specific growth rate (SGR) (p < 0.05) of alevins. The feed conversion ratio (FCR) in the 1.37% LA group was significantly lower than those in other groups (p < 0.05). The whole-body lipid content significantly decreased (p < 0.05) with dietary LA levels increasing from 0.74% to 2.00%. The fatty acid composition of the total lipid in muscle was closely correlated with those in the diets. The dietary LA level of 1.37% led to significantly higher activities of liver lipoprotein lipase (LPL) and hepatic lipase (HL) than those of other groups (p < 0.05). Hepatic malate dehydrogenase (MDH) and fatty acid synthase (FAS) decreased with the increase in the dietary LA levels from 0.11% to 1.37%. The lowest MDH and FAS activities were obtained in the 1.37% LA group (p < 0.05). This study indicated that an appropriate amount of dietary LA was beneficial for the growth and lipid metabolism of coho salmon alevins, and the results of the quadratic regression analysis of the SGR and FCR indicated that the optimal dietary LA requirements were 1.25% and 1.23% for coho salmon alevins, respectively.